Housing Development and Land Conversion at the Surrounding Area of Yogyakarta City - Su Ritohardoyo (Forum Geografi, 2001)
The acceleration urbanization has resulted in the growing number of housing in the rural area of surrounding city. As a consequence the size of converted agriculture land is also getting larger. However, the distribution of housing development and the impact on agriculture land have not yet been explored thoroughly through research. Therefore, this research aims at exposing rural-urbanization around city, housing development, and the conversion degree of agriculture land for housing. This research was carried out in the rural area around Yogyakarta city. It encompassed administrative divisions of Sleman and Bantul Districts. The research method is based on secondary data analysis. Several data are among other on population growth and housing distribution of 269 locations within the two districts. Data analysis employs of frequency and cross tabulation, statistics of regression and t test. Result of the research shows that rural-urbanization in around Yogyakarta has been so high. The proportion of rural-urbanized area has increased from 8.7 percents in 1980 to 43.5 percents in 1990, and 66.5 percents in the year of 2000. Similarly, the proportion of rural-urbanized population has increased from 13.2 percents in 1980 to 54.7 percents in 1990, and within 10 years (2000) it becomes 75.3 percents. Housing development of the rural area at the surrounding city was started with only 7 housing locations consisted of 59 units of building in 1973 to be 269 housing locations with 35.356 units of building in 2000. The rate of increase of the building 1.349 units per anum. The spatial and temporal characteristics of housing development of rural and urban area are different. In northern part of Yogyakarta, housing development has been growing since 1973 with the rate of growth 601 units per anum. In southern side of Yogyakarta, housing development in the rural area of Yogyakarta has been growing since 1980 with the rate of growth of 967 units per anum. Analysis result shows that number of construction in all housing site will reach 72.775 units in the year of 2025, out of wich 22.878 units will be in Bantul and 49.897 units in Sleman. The impact of the housing development is the conversion of mostly agriculture land, i.e. paddy field (67%), and only a small percentage are dry land and homestead. Within the last 27 years there has been 1,232.93 hectares of land conversion i.e. 1,068.45 hectares in Sleman and 164.47 hectares in Bantul. The rate of conversion in Sleman is 41.09 hectares per anum, whereas in Bantul it is 9.67 hectares per anum. It is predicted that land conversion in around Yogyakarta City in 2025 will be doubled to be 2.464 hectares. The distribution of this conversion will be dominant in Sleman, i.e. 2.123 hectares as compared to 341 hectares in Bantul.